Industrialization in Sub-Saharan Africa and import substitution policy - Mendes, Ana Paula F.; Bertella, Mário A. [UNESP]; Teixeira, Rudolph F. A. P. (Editora 34, 2014)
This article aims to contribute to the understanding of the process of import substitution in Sub-Saharan Africa. The process of industrialization in Sub-Saharan Africa occurred in two phases: a first step, even very early during the colonial regime began around the 1920s and ended in the late forties; a second phase of industrialization began in the late fifties and gained momentum in the sixties, when import substitution was implemented more widely. Although these countries were the last to embark on the strategy of import substitution, they followed the same steps of Latin American countries, and as the structural domestic and external constraints were too strong, the failure of the policy of import substitution arrived early and the negative impact on these economies had a greater magnitude.
Keywords: Sub-Saharan Africa; import substitution; industrialization